Understanding the intelligence cycle - Phythian, Mark. (London : Routledge, 2013)
"This book critically analyses the concept of the intelligence cycle, highlighting the nature and extent of its limitations and proposing alternative ways of conceptualising the intelligence process. The concept of the intelligence cycle has been central to the study of intelligence. As Intelligence Studies has established itself as a distinctive branch of Political Science, it has generated its own foundational literature, within which the intelligence cycle has constituted a vital thread - one running through all social-science approaches to the study of intelligence and constituting a staple of professional training courses. However, there is a growing acceptance that the concept neither accurately reflects the intelligence process nor accommodates important elements of it, such as covert action, counter-intelligence and oversight.Bringing together key authors in the field, the book considers these questions across a number of contexts: in relation to intelligence as a general concept, military intelligence, corporate/private sector intelligence and policing and criminal intelligence. A number of the contributions also go beyond discussion of the limitations of the cycle concept to propose alternative conceptualisations of the intelligence process. What emerges is a plurality of approaches that seek to advance the debate and, as a consequence, Intelligence Studies itself. This book will be of great interest to students of intelligence studies, strategic studies, criminology and policing, security studies and IR in general, as well as to practitioners in the field. "--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Intelligence service; National security; Electronic books